2020
DOI: 10.1175/jas-d-18-0355.1
|View full text |Cite
|
Sign up to set email alerts
|

How Does Hurricane Edouard (2014) Evolve toward Symmetry before Rapid Intensification? A High-Resolution Ensemble Study

Abstract: A 14-member high-resolution ensemble of Edouard (2014), a moderately sheared tropical storm that underwent rapid intensification (RI), is used to determine causes of vortex alignment and precipitation symmetry prior to RI. Half the members intensify similarly to the NHC’s best track, while the other seven ensemble members fail to reproduce intensification. Analyses of initial conditions (vertical wind shear, sea surface temperatures, relative humidity, vortex structure) reveal that lower humidity and weaker, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 83 publications
8
19
2
Order By: Relevance
“…The variation of rain is relatively subtle until 2 to 0 hr preceding the onset of RI, as rain content shows increasing trend when snow is depleted. Those changes are to some extent consistent with the results by a high-resolution numerical simulation (Alvey et al, 2020), in which, the solid condensate advected to the upper layer of up-shear side will sublimate and moisten the atmosphere, leading to axisymmetrization of precipitation and foreboding the occurrence of RI. Note that, although the value of CC in Figure 10 is small, the different trends of hydrometeor lutions preceding the onset of RI still exist between the different sets of Super TY cases, which is believed to be attributed to different dynamic and thermodynamic fields within the vortex.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The variation of rain is relatively subtle until 2 to 0 hr preceding the onset of RI, as rain content shows increasing trend when snow is depleted. Those changes are to some extent consistent with the results by a high-resolution numerical simulation (Alvey et al, 2020), in which, the solid condensate advected to the upper layer of up-shear side will sublimate and moisten the atmosphere, leading to axisymmetrization of precipitation and foreboding the occurrence of RI. Note that, although the value of CC in Figure 10 is small, the different trends of hydrometeor lutions preceding the onset of RI still exist between the different sets of Super TY cases, which is believed to be attributed to different dynamic and thermodynamic fields within the vortex.…”
Section: Discussionsupporting
confidence: 88%
“…According to the diagnoses using the Sawyer-Eliassen equation, Chen et al (2018) indicated that RI occurs when the RMW contraction reaches a certain degree, and enhanced additional microphysical diabatic heating at mid-levels and deep convection along with the surface friction facilitate earlier RMW contraction, causing the earlier RI. Recently, based on the ensemble simulations, Alvey et al (2020) indicated that the evaporation and sublimation of condensate that advected from the downshear quadrants moisten the middle to upper troposphere in the upshear quadrants of Hurricane Edouard (2014) in a sheared environment, which promotes an increase in precipitation axisymmetrization and leads to the onset of RI. Although some of prior conclusions showed that cloud microphysical processes may contribute to the onset of RI to some extent, a case study by numerical simulation or the use of low temporal-spatial-resolution or inconsecutive satellite observations still leave uncertainty of how the associated microphysical processes evolve surrounding the RI in TCs.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in the evolution between Figures 13 and 14, the mid and upper level vortices in the strong member became aligned more quickly than in the weak member, which was consistent with the observed evolution of the TC. This evolution of the two members, with the stronger member having stronger downshear convection near the TC center, earlier vortex alignment, and then greater symmetrization of precipitation (and increase in closure of stratiform precipitation prior to intensification), is consistent with the evolution of Hurricane Edouard 2014 as shown in both an observational study by Rogers et al [41] and an ensemble study by Alvey et al [35], and also with the intensification of Hurricane Earl (2010) in simulations [42].…”
Section: Structure Comparison Between Two Members and With Observationssupporting
confidence: 79%
“…A decrease of RMW 10 m , which leads to a larger Rossby number, is one such structural change that has been linked to RI onset [32]. Precipitation symmetry has also been shown to be a critical part of conditioning a vortex for rapid intensification [35,36], and these relationships imply that was true in the early intensification of Dorian. There is also a strong relationship (r = 0.88) between the initial intensity in the simulations and the intensity at 42 h, implying that some of the structure differences (and perhaps some of the large-scale initial differences discussed above) were tied to the initial state of the TC.…”
Section: Pweimentioning
confidence: 99%
“…While shear typically limits TC intensification, there are some situations where intensification can occur despite the presence of shear, particularly when the shear is of moderate strength (broadly defined as 850-200-hPa shear magnitudes ranging between 5 and 10 m s 21 ). This intensification can occur when there is forcing of strong convection downshear providing a significant projection onto wavenumber-0 (Reasor et al 2009;Nguyen and Molinari 2012), when precipitation and deep convection occur and persist on the upshear side (Jiang 2012;Stevenson et al 2014;Alvey et al 2015;Rogers et al , 2016Susca-Lopata et al 2015;Tao and Zhang 2015;Zawislak et al 2016;Nguyen et al 2017;Munsell et al 2017;Wadler et al 2018;Leighton et al 2018;Rios-Berrios et al 2018), and through downshear reformation (Molinari et al 2004(Molinari et al , 2006Molinari and Vollaro 2010;Nguyen and Molinari 2015;Chen et al 2018). The uncertain impacts of these processes in moderate shear is manifested as a pronounced forecasting challenge (Bhatia and Nolan 2013;Tao and Zhang 2015;Finocchio and Majumdar 2017), and this has been identified as a key challenge by the National Hurricane Center (NTSB 2017).…”
Section: Introductionmentioning
confidence: 99%